2022
DOI: 10.3390/ijerph19116952
|View full text |Cite
|
Sign up to set email alerts
|

The Kinematic and Kinetic Responses of the Trunk and Lower Extremity Joints during Walking with and without the Spinal Orthosis

Abstract: Spinal orthoses are an effective option for restoring the spine to its original position and controlling poor posture. However, the effects of poor posture and spinal orthoses on the kinematics and kinetics of trunk and lower extremity joints remain unclear. A six-camera Vicon motion capture system and two AMTI force plates were employed to collect gait parameters, including joint angle (spine, thorax, hip, knee, and ankle), range of motion (ROM), and ground reaction forces (GRFs). Furthermore, joint moments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Gait requires the combined movement of the joints and the surrounding muscles throughout the body with more significant movements in the joints of the lower limbs. The lower limb joints consist mainly of the hip, the knee, and the ankle, and the range of motion of each joint determines the soundness of the gait ( 2 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gait requires the combined movement of the joints and the surrounding muscles throughout the body with more significant movements in the joints of the lower limbs. The lower limb joints consist mainly of the hip, the knee, and the ankle, and the range of motion of each joint determines the soundness of the gait ( 2 , 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al conducted a study on the kinematics and dynamics of the trunk and the lower limb joints during walking in three different conditions: normal posture, poor posture, and with a spinal orthosis. The results obtained indicated that poor posture, such as an abnormal joint angle, has an impact on the kinematics and dynamics of the trunk during walking, which may be due to abnormal sensory inputs altering postural control (2,3). Vision is one of the primary sensory input organs, which effectively identifies the relative position of the body in space.…”
Section: Introductionmentioning
confidence: 99%